Breaking the Cycle of Divorce: Religious and Cultural Mediation by Kyai-Imams in Coastal Muslim Communities in Rembang and Melaka - Erfaniah Zuhriah; Erik Sabti Rahmawati; Faridatus Syuhadak; Risma Nur Arifah; Ahmad Qiram As-suvi (IBDA': Jurnal Kebudayaan Islam)
This research endeavours to critically examine the role of cultural mediation by Kyai and Imam in mitigating the incidence of divorce within coastal Muslim communities in Rembang and Melaka. It seeks to understand how these religious leaders influence social dynamics and foster community cohesion, stabilizing familial relationships in these regions. The research used a qualitative approach with interview methods with religious leaders, community members, and legal professionals to identify the social, religious, and legal roles of Kyai and Imam as mediators in family conflicts. The findings reveal that Kyai and Imam are crucial in guiding troubled couples through domestic conflict by integrating religious teachings and formal legal regulations. Kyai and Imams provide spiritual advice and authoritative figures capable of providing practical solutions to resolving family problems. However, challenges related to accessibility to formal mediation and the limitations of informal mediation point to the need for strengthened integration between religious patronage and the state legal system. The study concludes that Kyai and Imam patronage significantly reduces divorce rates. However, closer collaboration between the formal legal and faith-based mediation mechanisms is needed to increase effectiveness. This study offers a fresh perspective on the connections among religion, legal systems, and family mediation within Muslim communities.